The potential role of micro- and nanoplastics in the spread of viruses - B. G. Andryukov; N. N. Besednova; T. S. Zaporozhets; A. A. Yakovlev; E. V. Matosova; S. P. Kryzhanovsky; M. Yu. Shchelkanov (Антибиотики и Химиотерапия, 2023)
The review presents recent materials about the growing influence of micro- and nanoplastics (MP/NP) on the spread of pathogenic viruses in humans and animals. The issue of the interaction of viruses with the plastisphere, the role of the virus envelope in the preservation of these microorganisms on microparticles in the composition of the biofilm has been elucidated. The issues of synergism of the pathogenetic action of MP/NP and viruses, studied on various models, are discussed. The article shows the negative effect of MP/NP on the permeability of the body's natural barriers, which can create favorable conditions for the penetration of viruses and the development of an infectious process. The authors draw attention to the need to expand interdisciplinary research in this area, given the fact that viruses residing on MP/NP can increase their infectivity and, possibly, form new genovariants.